2018
DOI: 10.1002/jmri.25940
|View full text |Cite
|
Sign up to set email alerts
|

REnal Flow and Microstructure AnisotroPy (REFMAP) MRI in Normal and Peritumoral Renal Tissue

Abstract: 2 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…For each b value range, the maximum and average b values were also computed. Monoexponential DWI studies provided ADC values [20,21,43,[47][48][49][50][51][52][53][54][55][56][57][58][59][60][61], DTI studies provided MD and FA values [29,32,33,38,42,45,[62][63][64][65][66][67][68][69][70][71] and IVIM studies provided D, f and D* values [20,21,28,29,32,42,43,54,55,68,[71][72][73][74][75][76]…”
Section: Literature Review and Data Extractionmentioning
confidence: 99%
“…For each b value range, the maximum and average b values were also computed. Monoexponential DWI studies provided ADC values [20,21,43,[47][48][49][50][51][52][53][54][55][56][57][58][59][60][61], DTI studies provided MD and FA values [29,32,33,38,42,45,[62][63][64][65][66][67][68][69][70][71] and IVIM studies provided D, f and D* values [20,21,28,29,32,42,43,54,55,68,[71][72][73][74][75][76]…”
Section: Literature Review and Data Extractionmentioning
confidence: 99%
“…MRI provides important information regarding the renal vascular anatomy, correlation of the tumor with the collecting system, its vicinity to the renal hilum, and the endophytic-exophytic nature of the tumor, which help predict the difficulties of performing a PN (39). Moreover, MRI may provide information regarding intrarenal differences in blood flow, perfusion, oxygenation, and structural properties of kidney tissue (40). If these images could be superimposed real time during robotic PN, similarly to what is done for MRI-fusion prostatic biopsy, guidance during tumor resection would be largely facilitated, allowing exact tumor resection with maximal renal preservation.…”
Section: What the Urologist Expects From A Renal Mrimentioning
confidence: 99%
“…The diffusion (diffusion coefficient, D ) and perfusion parameters (perfusion‐related pseudo‐diffusion coefficient, D * , and perfusion fraction, f ) are typically estimated from IVIM signals using a double‐exponential model with an assumption that the movement of water can be described by hindered diffusion in extravascular tissue and flow in capillary networks . Recent studies have indicated that IVIM‐MRI can detect the direction‐dependent flows in the heart, kidney, skeletal muscle and brain as D * and f in anisotropic capillary networks depend on the direction of the diffusion gradient . The directional sensitivity of the IVIM signal to flow may allow characterization and monitoring of the direction‐dependent flow network in cerebral vasculature, especially in small animal models of ischemia.…”
Section: Introductionmentioning
confidence: 99%